Pemberdayaan Pengrajin Perak Melalui Market Place sebagai Media Penjualan Online di Desa Ungga,Kabupaten Lombok Tengah - Khairan Marzuki; Apriani Apriani; Ni Gusti Ayu Dasriani (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The impact of the industrial revolution era 4.0 has been switched from a traditional system to a digital. Therefore, craftsmen also must follow the changing of this era to sell their handicrafts that previously used a traditional sales system where buyers have to go to the counter/gallery selling silver, especially the silver handicrafts in the village of Lombok, Central Lombok. The output of this community service is that craftsmen have an online shop as a medium for selling the silver handicrafts in Ungga. This online shop can be accessed by residents all over the world anytime and anywhere in making an online store uses the word press content management system because it probably solves the problem to increase the product sales.